化简(-2)(-2)^1996+(-2)^1997+(-2)^1998的结果是() A.-2^1996 B.2^1996 C.0 D .3*2^1996

来源:学生作业帮助网 编辑:六六作业网 时间:2024/07/08 12:12:15
化简(-2)(-2)^1996+(-2)^1997+(-2)^1998的结果是()A.-2^1996B.2^1996C.0D.3*2^1996化简(-2)(-2)^1996+(-2)^1997+(-2

化简(-2)(-2)^1996+(-2)^1997+(-2)^1998的结果是() A.-2^1996 B.2^1996 C.0 D .3*2^1996
化简(-2)(-2)^1996+(-2)^1997+(-2)^1998的结果是() A.-2^1996 B.2^1996 C.0 D .3*2^1996

化简(-2)(-2)^1996+(-2)^1997+(-2)^1998的结果是() A.-2^1996 B.2^1996 C.0 D .3*2^1996
(-2)(-2)^1996+(-2)^1997+(-2)^1998
=(-2)^1997-2^1997+2^1998
=-2^1997-2^1997+2×2^1997
=(-1-1+2)×2^1997
=0
选C